Kedwibahasaan Karyawan Pariwisata Kabupaten Gianyar, Bali - Pradnya Wati, Anak Agung; Simpen, I Wayan; Arnati, Ni Wayan (Humanis, 2018)
This research entitled "Bilingual of Employee Tourism in Gianyar Regency, Bali". The purpose of this research is to know the bilingual of tourism employee in Gianyar based on topic, situation, aspect, and causal factor. The theory used is a sociolinguistic theory that was discovered by Mackey and Fishman. Methods and techniques of data collection used is a method refer to instrument techniques, see libat ably, and record. In the data analysis phase using qualitative and quantitative methods. In the presentation stage of data analysis using informal and formal methods. The population of this study is the entire employees engaged in tourism in Gianyar regency, Bali. The sample of this study was sixty respondents. Based on the analysis that has been done is known that employees working in the field of tourism in Gianyar mastered two to three languages. The modern topic of the language office realm that is often used is Indonesian, while for traditional topics the language is often used is the local language. For situations in the realm of the office, formal situations use the Indonesian language, whereas in informal situations often use local languages. Modern and traditional topics in the domestic realm of informal situations use local languages, namely Balinese and Javanese. However, the most widely encountered is the Balinese language. The Balinese language consists of two types, namely high and low. The high variety used by triwangsa and low variety is used by employees not triwangsa. In addition, the factors that cause bilinguality among employees are internal and external factors. Internal factors, namely age, gender, and daily life of respondents. External factors, ie speech, topic, and speaker contact. The biggest factor is the external factor.